2016
DOI: 10.2174/1874210601610010460
|View full text |Cite
|
Sign up to set email alerts
|

Dental Occlusion and Ophthalmology: A Literature Review

Abstract: Stomatognathic system is strictly correlated to other anatomical regions; many studies investigated relationship between temporomandibular joint and posture, several articles describe cranio-facial pain from dental causes, such as trigger points. Until now less interest has been given to connections between dental occlusion and ophthalmology, even if they are important and involving. Clinical experience in dental practice claims that mandibular latero-deviation is connected both to eye dominance and to defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
0
29
0
2
Order By: Relevance
“…In sleep apnea patients, the mandibular position is abnormal, in part because during sleep, the tongue is more retruded than in healthy people [41, 42]. Functionally, the mandible, neck/head, and tongue are strictly associated in some reflex activities which induce a perpetual arrangement of reciprocal muscular tone [43, 44]. Stimulation of the lingual nerve, sensorial secondary branch of mandibular division of the trigeminal nerve (CN Vdiv3), determines the discharge of hypoglossal nerve fibers which concurrently cause tongue retrusion [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sleep apnea patients, the mandibular position is abnormal, in part because during sleep, the tongue is more retruded than in healthy people [41, 42]. Functionally, the mandible, neck/head, and tongue are strictly associated in some reflex activities which induce a perpetual arrangement of reciprocal muscular tone [43, 44]. Stimulation of the lingual nerve, sensorial secondary branch of mandibular division of the trigeminal nerve (CN Vdiv3), determines the discharge of hypoglossal nerve fibers which concurrently cause tongue retrusion [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the intermediate nucleus of the medulla, the proprioception of suboccipital muscles, sternocleidomastoid, and trapezius is monosynaptical and related with the nucleus of the twelfth cranial nerves and with the nucleus of the solitary tract, this justifying the functional union among neck, head, and tongue and the vegetative answers inducted by postural variations of every element of this circuit. Among them are also some afferent fibers to the intermediate nucleus coming from vestibular and oculomotor nucleus [44]. It is also interesting to note that the tongue posture, position of apex of the tongue, and freeway space are correlated to watchfulness and mood.…”
Section: Discussionmentioning
confidence: 99%
“…The Medium Longitudinal File, which allows a direct connection between the various cranial nerves, can provide a way to link the upper spinal cord to the mesencephalus. The ELIBA® works by way of proprioception and interception, in which it stimulates the trigeminal system and, consequently, activates the oculomotor system to help maintain appropriate tongue position and movement [28]. Contact of the tongue apex with its designated spot during the night together with perioral muscle-generated centripetal force is indicative of functional improvement.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, the characteristic of individuals with myogenic pain appear to be related to difficulties in adapting to variations in their visual input rather than absolute values of a single test or condition (e.g., eyes closed or open). In general, we propose that a relationship exists between refractive disorders, vision disorders, the stomatognathic system, and EMG hyperactivity, as described in a recent literature review [7]. It has been reported that the prevalence of vision disorders in the general population is high, and it is increasing in Europe and elsewhere worldwide [8,9].…”
Section: Introductionmentioning
confidence: 98%